Destiny Of The Sands Of Time In Mike Newell Movie Entitled Prince Of Persia (2010): A Individual Psychological Approach - Hastuti, Fitria Sri, Drs. Abdillah Nugroho, M. Hum., Siti Fatimah, S. Pd, M. Hum (2013)
The major problem of this study is how is the Destiny of the Sands of Time reflected in Prince of Persia's Movie based on Individual Psychological Approach. This study focuses on analyzing the characteristic of Dastan as main character in Prince of Persia Movie. This study uses two data source, namely primary and secondary data source. The primary data source of the study is the movie Prince of Persia directed by Mike Newell, while the secondary data including the scrip of the movie and the other information from the book and website from internet that were relevant to the subject matter. The method of data collection is qualitative method. Based on the analysis, the study of this research comes from the major character problem. The researcher using an individual psychological approach that appropriate to analyses the relationship between the theory and the movie. All those steps the researcher hope it will answer the goal of this research.